2004
DOI: 10.1104/pp.104.040113
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Tandem-Duplicated P450 Genes SPS/BUS/CYP79F1 and CYP79F2 in Glucosinolate Biosynthesis and Plant Development by Ds Transposition-Generated Double Mutants

Abstract: A significant fraction (approximately 17%) of Arabidopsis genes are members of tandemly repeated families and pose a particular challenge for functional studies. We have used the Ac-Ds transposition system to generate single-and doubleknockout mutants of two tandemly duplicated cytochrome P450 genes, SPS/BUS/CYP79F1 and CYP79F2. We have previously described the Arabidopsis supershoot mutants in CYP79F1 that exhibit massive overproliferation of shoots. Here we use a cytokinin-responsive reporter ARR5::uidA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 41 publications
7
73
1
2
Order By: Relevance
“…This result resembles the cytokinin overproduction phenotype, in that cytokinin is known to break apical dominance and increase the thickness of the stem (29,30). In Arabidopsis CYP79F1 knockout mutants, cytokinin accumulated to the highest level at the leaf axil, although the CYP79F1 overexpression lines did not show any phenotypic difference (15,25,26). Hence, it has been suggested that the CYP79F1 gene may modulate cytokinin level at the site of bud initiation and the changes in cytokinin levels at these sites are responsible for the altered shoot branching pattern (15).…”
Section: Phenotypes Of Transgenic Plantsmentioning
confidence: 86%
See 1 more Smart Citation
“…This result resembles the cytokinin overproduction phenotype, in that cytokinin is known to break apical dominance and increase the thickness of the stem (29,30). In Arabidopsis CYP79F1 knockout mutants, cytokinin accumulated to the highest level at the leaf axil, although the CYP79F1 overexpression lines did not show any phenotypic difference (15,25,26). Hence, it has been suggested that the CYP79F1 gene may modulate cytokinin level at the site of bud initiation and the changes in cytokinin levels at these sites are responsible for the altered shoot branching pattern (15).…”
Section: Phenotypes Of Transgenic Plantsmentioning
confidence: 86%
“…For the process of core structure formation, the methionine-condensed products are first converted into aldoxime by CYP79F1 and CYP79F2, which metabolize the short and long-chain (Met1-6) and only the long-chain methionine (Met5, 6), respectively (14). Aliphatic glucosinolate biosynthesis is completely abolished in the double-knockout Arabidopsis mutant sps-7cyp79F2-1 (15). Aldoximes are generally unstable and toxic, and subsequently they do not accumulate within the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Ac/Ds tagging systems have been utilized to isolate a number of genes (Bancroft et al 1993;Jones et al 1994;James et al 1995;Bhatt et al 1996;Meissner et al 1999), to define promoter and enhancer elements (Sundaresan et al 1995;Chin et al 1999;Greco et al 2003;Wu et al 2003;Jin et al 2004), and to create genetic mosaics for clonal analysis (Peng and Harberd 1997;Jenik and Irish 2001). The tendency of Ds to transpose to linked sites has also been exploited to disrupt genes present in tandem arrays (Takken et al 1999;Tantikanjana et al 2004) and to perform localized saturation mutagenesis (Nishal et al 2005). Ac/Ds mutagenesis platforms in Arabidopsis (Sundaresan et al 1995;Ito et al 1999;Muskett et al 2003;Kuromori et al 2004), tomato (Healy et al 1993;Knapp et al 1994;Meissner et al 2000), tobacco (Scofield et al 1992), rice (Chin et al 1999;Zheng-Ge et al 2003;Kim et al 2004;Kolesnik et al 2004), and barley (Koprek et al 2000;Cooper et al 2004) have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The following cytosolic steps involve oxidation of the chainelongated amino acid to an aldoximine catalyzed by the cytochrome P450 monooxygenases CYP79F1 and CYP79F2 (Hansen et al, 2001;Reintanz et al, 2001;Chen et al, 2003;Tantikanjana et al, 2004). A second oxidation step leads to an aci-nitro compound, catalyzed by CYP83A1 (Hemm et al, 2003;Naur et al, 2003), which is then conjugated with a sulfur donor into S-alkyl thiohydroximate.…”
Section: Introductionmentioning
confidence: 99%